(untitled) (The Pakistan Development Review, 1991)
It has been argued in the literature that. capital formation is the key to economic development. Apart from expansion in productive capacity, capital formation is also a source of embodied technical change and progressive modernization. Although aid could be a source of capital formation, it is undependable and inconsistent with the phrase that capital is made at home [Nurkse (1953)]. Agriculture, being a sector of major proportions in developing countries holds a pivotal position as a major contributor to capital formation. In the early stages of economic deVelopment, it must fund industrialization, finance capital imports and act as a ready market for industrial goods. It may, however, be remembered that agricUlture can play this role only within certain limits and that excessive resource transfers from agricUlture can prove to be self-defeating and must be avoided [Timmer (1988)]. What has been the role of Pakistan’s agriculture in this respect, is a controversial issue. There are studies [Hamid (1970); Khan (1985) and Qureshi (1987)] that hold that agriculture’s role in capital formation in Pakistan has, at best, been dismal. Others [Chaudhry (1973); Government of Pakistan (1986, 1988)] have argued that agriculture in Pakistan was heavily taxed and made significant contributions to economic de,:elopment. The controversy arises as the former set of studies dealt with direct taxes alone as against the coverage of local and indirect taxes and taxes implicit in price and exchange rate policies in the latter.